PROFIL PEMECAHAN MASALAH SISWA KELAS VII SMP NEGERI 3 PAMONA TIMUR PADA MATERI PECAHAN DITINJAU DARI KEMAMPUAN MATEMATIKA: PROFILE OF PROBLEM SOLVING OF CLASS VII STUDENTS AT SMP NEGERI 3 PAMONA TIMUR IN FRACTION MATERIAL IDENTIFIED THROUGH THE ABILITY OF MATHEMATICS - Rumba, Kevin Angryawan; Awuy, Evie; Lefrida, Rita; Alfisyahra (Universitas Tadulako, 2023)
This study aims to obtain an overview of fractional problem solving in terms of mathematical ability in class VII students of SMP Negeri 3 Pamona Timur. This research is a descriptive qualitative research. The research subjects consisted of three students with high, medium and low abilities. Data collection techniques in this study were written tests and interviews. The results of this study indicate that the subject's ability to solve fraction problems according to Polya's stages are as follows: (1) the stages of understanding the problem of high, medium, and low ability subjects read repetitive problems, mention information that is known based on declarative sentences and information asked based on imperative sentences or question of the problem appropriately. (2) the stage of preparing a problem solving plan for subjects with high, medium, and low abilities in making a problem solving plan, namely stating the information asked to make a mathematical model in the form of adding and subtracting fractions based on what is known correctly. (3) the stage of carrying out the problem-solving plan, high-ability subjects carry out the problem-solving plan in accordance with what has been planned correctly, while subjects with moderate and low ability carry out the problem-solving plan according to what was planned beforehand but not quite right. (4) the stage of re-examining the results of solving high-skilled subjects did not write down how to check answers, but when interviewed by researchers, high-skilled subjects were able to re-check the answers that had been written down. Meanwhile, subjects with medium and low abilities were sure of their answers and did not re-check their answers, because they did not understand how to re-check their answers